Animal Suffering and Public Relations: The Ethics of Persuasion in the Animal-Industrial Complex - Almiron, Núria (Routledge New Directions in PR & Communication Research, 2023)
Animal Suffering and Public Relations conducts an ethical assessment of public relations, mainly persuasive communication and lobbying, as deployed by some of the main businesses involved in the animal-industrial complex—the industries participating in the systematic and institutionalised exploitation of animals. Society has been experiencing a growing ethical concern regarding humans’ (ab)use of other animals. This is a trend first promoted by the development of animal ethics—which claims any sentient being, because of sentience, deserves moral consideration—and more recently by other approaches from the social sciences, including critical animal studies. In this volume, we aim to start an entirely unaddressed discussion within the field of public relations: The need to problematise the ethics of persuasion when nonhuman animal suffering is involved, particularly the impact of persuasion and lobbying on compassion towards other animals in the cases of food, experimentation, entertainment, and environmental management. This book provides an interdisciplinary, theoretical discussion illustrated with international case studies from experts in strategic communication, public relations, lobbying and advocacy, animal ethics, philosophy of law, political philosophy, and social psychology. This unique book merges the fields of critical public relations, animal ethics, and critical animal studies and will be of direct appeal to a wide range of researchers, academics, and doctoral students across related fields. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.